Crucial Elements in the Development of Cyber Security Strategies in Saudi Arabia - Zafar, Nisar Ahmad; Khan, Shahzad Ali (Journal of Accounting, Business and Management (JABM), 2024)
The digital world has gained significant importance in recent years, owing to its many advantages as well as the sheer volume of users, which is constantly increasing, including in both public and private organizations. Numerous hazards and vulnerabilities associated with this growth and advancement have been interfering from time to time. As a result, cybersecurity and protection measures have been implemented in different digital domains. The national security, the economy, business, and the everyday lives of people are constantly under threat due to the innate weaknesses in cyberspace and the continually growing threat of cyber attacks. The research paper highlights essential elements in developing and managing cyber security strategies in Saudi Arabia to strengthen security measures. To achieve this motive, a literature review has been done to explore the significance of cyber security elements such as security awareness through education, risk prevention, data management, network security in business and smart cities, and constant monitoring of security measures by analyzing previous studies so that Saudi Arabia can better develop its cyber security policies by incorporating these elements into latest policies. The use of Artificial Intelligence (AI) in cyber security is also being explored in this study due to the fast penetration of AI worldwide. This paper is also helpful for policymakers in designing national cyber security policies by examining the guidelines given at the end of the study.